2017
DOI: 10.1155/2017/8365762
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Histone H3 Lysine 9 Methylation Contributes to the Pathogenesis of Latent Autoimmune Diabetes in Adults via Regulation of SUV39H2 and KDM4C

Abstract: Aims. Latent autoimmune diabetes in adults (LADA) is an autoimmune disease of which the mechanism is not clear. Emerging evidence suggests that histone methylation contributes to autoimmunity. Methods. Blood CD4+ T lymphocytes from 26 LADA patients and 26 healthy controls were isolated to detect histone H3 lysine 4 and H3 lysine 9 methylation status. Results. Reduced global H3 lysine 9 methylation was observed in LADA patients' CD4+ T lymphocytes, compared to healthy controls (P < 0.05). H3 lysine 4 methylatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“… 85,101 Dysregulation of SUV39H2 has also been reported in several other diseases, such as hereditary nasal parakeratosis, which is caused by a mutation of SUV39H2 in dogs. 102 Moreover, it has been reported that alterations in the regulation of SUV39H2 are also associated with autoimmune diabetes 103 and steatohepatitis in mice. 104 …”
Section: Introductionmentioning
confidence: 99%
“… 85,101 Dysregulation of SUV39H2 has also been reported in several other diseases, such as hereditary nasal parakeratosis, which is caused by a mutation of SUV39H2 in dogs. 102 Moreover, it has been reported that alterations in the regulation of SUV39H2 are also associated with autoimmune diabetes 103 and steatohepatitis in mice. 104 …”
Section: Introductionmentioning
confidence: 99%
“…A mutation of SUV39H2 was reported to be responsible for hereditary nasal parakeratosis [ 19 ]; this provided us insights into SUV39H2-mediated epigenetic regulation in keratinocytes. Additionally, dysregulation of SUV39H2 mediated by H3K9me3 is associated with autoimmune diabetes [ 20 ] and steatohepatitis [ 21 ] in mice. The activity of SUV39H2 is modulated in various manners.…”
Section: Introductionmentioning
confidence: 99%
“…SUV39H2 downregulation has been also associated with autoimmune diseases. Decreased expression levels of SUV39H2 and reduction of global H3 lysine 9 methylation has been evidenced in CD4+ T cells from Latent autoimmune diabetes patients [ 73 ]. These data correlate with the miRNAs pattern of CD patients found in this study (Fig.…”
Section: Discussionmentioning
confidence: 99%